تحليل محتوى الاستماع في كتاب "دروس اللغة العربية" للصف الأول للمدرسة الثانوية الإسلامية للطبعة ٢٠٢٠ - Muhammad Qadhafi; Soraiya Mohammad Usman (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2023)
Through this research, the researcher tries to identify the contents of Listening skills in the Arabic textbook “Durusu al-lughah al-Arabiyah,” which applies 2013 curriculum (KMA 183, 2019) for first-grade students of Islamic senior high schools, printed in 2020. This study was conducted by qualitative research and employed the “descriptive analysis technique.” The population of this study is the Arabic textbook “Durusu al-lughah al-Arabiyah,” which applies the 2013 curriculum for first-grade students of Islamic senior high schools. The data collection procedures include: making a checklist, analyzing the textbook content, coding, tabulating data, and concluding. The result of the research found that both listening skills material in the textbook “Durusu al-lughah al-Arabiyah” which applies the 2013 curriculum for first-grade students of Islamic senior high schools, is good material according to Abd al-Rahman ibn Ibrahim al-Fauzan in his book “Idla’at li Mu’alimi al-lughah al-Arabiyah li Ghairi Nathiqin Biha.” However, the Content Listening subject in the textbook “Durusu al-lughah al-Arabiyah” are relevant to the curriculum of 2013 (KMA 183, 2019) in Arabic subject for the first class in the Islamic senior high school.